Modification of pristine multiwalled carbon nanotube by grafting with poly(methyl methacrylate) using benzoyl peroxide initiator - Ali, Umar (Wiley Periodicals, 2016)
Multiwalled carbon nanotube was successfully grafted with poly(methyl methacrylate) by free radical mechanism using benzoyl peroxide initiator. The reaction was carried out in situ, where the initiator and methyl methacrylate monomer generated the polymer-free radical that was subsequently grafted to the surface of the pristine multiwalled carbon nanotube. The multiwalled carbon nanotube grafted poly(methyl methacrylate) (MWCNT-g-PMMA) were characterized using Fourier transform infrared, differential scanning calorimetry, thermogravimetric analysis, 13 C-solid NMR spectroscopy, X-ray photoelectron spectroscopy, and scan electron microscopy. From the result of the characterizations, the grafting of poly(methyl methacrylate) on to multiwalled carbon nanotube was confirmed, and a percentage grafting of 41.51% weight was achieved under optimized conditions with respect to the temperature and the amount of the initiator.